Universal Credit and other in-work benefits - a guide for union reps and workers - Oates, Andrea (London, 2019)
"This latest edition of the Labour Research Department’s annual guide to welfare benefits takes account of the major changes in the benefits system, in particular the introduction and roll-out of Universal Credit. Universal Credit and other in-work benefits focuses on the types and rates of in-work benefits available, and includes any changes to the rules for claiming them from 6 April 2019. Trade unionists can play an important role in helping members and their families claim the in-work benefits they are entitled to, billions of which go unclaimed. This booklet aims to help make reps aware of the latest reforms so they can give accurate initial advice."